A Case of Iliopsoas Hematoma in a Patient on Acenocoumarol - Parunandi, Yashaswini; Shenkeshi, Suvarchala; Tanniru, Samatha; Mitta, Sandeep Goud (Indian Journal of Pharmacy Practice)
The iliopsoas hematoma is a rare condition that can result from various factors, such as trauma, anticoagulant use, iatrogenic injury during lumbar procedures, and bleeding disorders. Bleeding complications are expected to become more common with the increasing use of anticoagulants. We present the case of a 53-year-old female with a known history of Chronic Rheumatic Heart Disease (CRHD) and Mitral valve Stenosis (MS), who had previously undergone Mitral Valve Repair (MVR). Since then, she had been on oral Acenocoumarol therapy. Over time, her prothrombin time and International Normalized Ratio (INR) gradually became deranged. The patient’s condition stabilized after reducing the dose of Acenocoumarol.
Keywords: Acenocoumarol; Anticoagulants; Iliopsoas Hematoma; International Normalized Ratio